TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENCURIAN YANG DILAKUKAN OLEH ANAK DIBAWAH UMUR MENURUT UU RI NOMOR 11 TAHUN 2021 TENTANG SISTEM PERADILAN PIDANA ANAK - Rikha Dewi Fitria; Margo Hadi Pura (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Criminal law is the whole of the regulations that determine what actions are prohibited and are included in criminal acts, and determine what penalties can be imposed on those who commit them. While a criminal act is an act that is prohibited by a rule of law, which prohibition is accompanied by threats (sanctions) in the form of certain crimes, for anyone who violates these rules. A criminal act is an act that is prohibited by a rule of law, which prohibition is accompanied by threats (sanctions) in the form of certain crimes, for anyone who violates these rules. While theft is a language (etymology) theft comes from the word steal which has a pe- prefix and an suffix. The word steal itself means taking someone else's property without permission or illegally, usually in secret. According to the Big Indonesian Dictionary, the meaning of the word steal is to take someone else's property without permission or illegally, usually in secret. Sedafkan meaning of theft is a process, a way of doing. Child is a boy or girl who has not matured or has not experienced puberty. A child is a person in the case of a naughty child who has reached the age of 8 (eight years) but has not yet reached the age of 18 (eighteen years) and has never been married.